A land of milk and honey with streets paved with gold: do emigrants have over-optimistic expectations about incomes abroad? - David McKenzie; John Gibson; Steven Stillman (Institute for the Study of Labor (IZA), 2007)
Millions of people emigrate every year in search of better economic and social opportunities. Anecdotal evidence suggests that emigrants may have over-optimistic expectations about the incomes they can earn abroad, resulting in excessive migration pressure, and in disappointment amongst those who do migrate. Yet there is almost no statistical evidence on how accurately these emigrants predict the incomes that they will earn working abroad. In this paper we combine a natural emigration experiment with unique survey data on would-be emigrants' probabilistic expectations about employment and incomes in the migration destination. Our procedure enables us to obtain moments and quantiles of the subjective distribution of expected earnings in the destination country. We find a significant under-estimation of both unconditional and conditional labor earnings at all points in the distribution. This under-estimation appears driven in part by potential migrants placing too much weight on the negative employment experiences of some migrants, and by inaccurate information flows from extended family, who may be trying to moderate remittance demands by understating incomes.
urn:nbn:de:101:1-20080401425
Keywords: 330; Migranten; Internationale Wanderung; Lohn; Erwartungstheorie